UPPER TRIASSIC TO CRETACEOUS RADIOLARIA FROM NICARAGUA AND NORTHERN COSTA RICA - THE MESQUITO COMPOSITE OCEANIC TERRANE - Baumgartner, Peter O.; Flores, Kennet; Bandini, Alexandre N.; Girault, France; Cruz, Daniel (Ofioliti, 2008)
We propose a new terrane subdivision of Nicaragua and Northern Costa Rica, based on Upper Triassic to Upper Cretaceous radiolarian biochronology of ribbon radiolarites, the newly studied Siuna Serpentinite Mélange, and published 40Ar/39Ar dating and geochemistry of mafic and ultramafic igneous rock units of the area.The new Mesquito Composite Oceanic Terrane (MCOT) comprises the southern half of the Chortis Block, that was assumed to be a continental fragment of N-America. The MCOT is defined by 4 corner localities characterized by ultramafic and mafic oceanic rocks and radiolarites of Late Triassic, Jurassic and Early Cretaceous age: 1. The Siuna Serpentinite Mélange (NE-Nicaragua), 2. The El Castillo Mélange (Nicaragua/Costa Rica border), 3.The Santa Elena Ultramafics (N-Costa Rica) and, 4. DSDP Legs 67/84.1. The Siuna Serpentinite Mélange contains, high pressure metamorphic mafics and Middle Jurassic (Bajocian-Bathonian) radiolarites in original, sedimentary contact with arc-metandesites. The Siuna Mélange also contains Upper Jurassic black detrital chert formed in a marginal (fore-arc?) basin shortly before subduction. A phengite 40Ar/39Ar -cooling age dates the exhumation of the high pressure rocks as 139 Ma (earliest Cretaceous).2. The El Castillo Mélange comprises a radiolarite block tectonically embedded in serpentinite that yielded a diverse Rhaetian (latest Triassic) radiolarian assemblage, the oldest fossils recovered so far from S-Central America.3. The Santa Elena Ultramafics of N-Costa Rica together with the serpentinite outcrops near El Castillo (2) in Southern Nicaragua, are the southernmost outcrops of the MCOT. The Santa Elena Unit (3) itself is still undated, but it is thrust onto the middle Cretaceous Santa Rosa Accretionary Complex (SRAC), that contains Lower to Upper Jurassic, highly deformed radiolarite blocks, probably reworked from the MCOT, which was the upper plate with respect to the SRAC.4. Serpentinites, metagabbros and basalts have long been known from DSDP Leg 67/84 (3), drilled off Guatemala in the Nicaragua-Guatemala forearc basement. They have been restudied and reveal 40Ar/39Ar dated Upper Triassic to middle Cretaceous enriched Ocean Island Basalts and Jurassic to Lower Cretaceous depleted Island arc rocks of probable Pacific origin.The area between localities 1-4 is largely covered by Tertiary to Recent arcs, but we suspect that its basement is made of oceanic/accreted terranes. Earthquake seismic studies indicate an ill-defined, shallow Moho in this area. The MCOT covers most of Nicaragua and could extend to Guatemala to the W and form the Lower (southern) Nicaragua Rise to the NE. Some basement complexes of Jamaica, Hispaniola and Puerto Rico may also belong to the MCOT.The Nicoya Complex s. str. has been regarded as an example of Caribbean crust and the Caribbean Large Igneous Province (CLIP). However, 40Ar/39Ar - dates on basalts and intrusives indicate ages as old as Early Cretaceous. Highly deformed Jurassic and Lower Cretaceous radiolarites occur as blocks within younger intrusives and basalts. Our interpretation is that radiolarites became first accreted to the MCOT, then became reworked into the Nicoya Plateau in Late Cretaceous times. This implies that the Nicoya Plateau formed along the Pacific edge of the MCOT, independent form the CLIP and most probably unrelated with he Galapagos hotspot.No Jurassic radiolarite, no older sediment age than Coniacian-Santonian, and no older 40Ar/39Ar age than 95 Ma is known from S-Central America between SE of Nicoya and Colombia. For us this area represents the trailing edge of the CLIP s. str.